Bioethanol - Brazil, 30 years of Proálcool - Andrietta, M. G. S.; Andrietta, S. R.; Steckelberg, C.; Stupiello, E. N A [UNESP] (My University, 2007)
Brazil, which has always been in the forefront of sugarcane production, also occupies a prominent position as the first country to produce and use biofuel in its automobile fleet. This fact is a consequence of the introduction of a program which has already turned 30 years, the Próalcool (National Alcohol Program). The oil crisis in the seventies encouraged the government to develop an alternative way to replace gasoline. Bioethanol was then born as fuel obtained from fermentation of sugarcane juice, molasses or both. In the eighties, 85% of the cars ran exclusively on alcohol. Ethanol production in that decade exceeded sugarcane production by the mills. The installed units reached in that period the capacity to produce 18 billion liters of bioethanol per season, a volume equivalent to 100 million barrels of gasoline. The fermentation process, which so far had been restricted to manufacturing sugarcane liquor (aguardente) or ethanol as a byproduct of sugarcane, takes over the spotlight in the entrepreneurial scene. As a result, processes comprising engineering concepts came up and most of the biological phenomena involved in fermentation were understood. The knowledge gathered and the units installed have granted Brazil the hold of production technology and use of a clean fuel.